A Direct Comparison of Local-Global Integration in Autism and other Developmental Disorders: Implications for the Central Coherence Hypothesis - Bernardiono, I (2012)
The weak central coherence hypothesis represents one of the current explanatory models in Autism Spectrum Disorders (ASD). Several experimental paradigms based on hierarchical figures have been used to test this controversial account. We addressed this hypothesis by testing central coherence in ASD (n = 19 with intellectual disability and n = 20 without intellectual disability), Williams syndrome (WS, n = 18), matched controls with intellectual disability (n = 20) and chronological age-matched controls (n = 20). We predicted that central coherence should be most impaired in ASD for the weak central coherence account to hold true. An alternative account includes dorsal stream dysfunction which dominates in WS. Central coherence was first measured by requiring subjects to perform local/global preference judgments using hierarchical figures under 6 different experimental settings (memory and perception tasks with 3 distinct geometries with and without local/global manipulations). We replicated these experiments under 4 additional conditions (memory/perception*local/global) in which subjects reported the correct local or global configurations. Finally, we used a visuoconstructive task to measure local/global perceptual interference. WS participants were the most impaired in central coherence whereas ASD participants showed a pattern of coherence loss found in other studies only in four task conditions favoring local analysis but it tended to disappear when matching for intellectual disability. We conclude that abnormal central coherence does not provide a comprehensive explanation of ASD deficits and is more prominent in populations, namely WS, characterized by strongly impaired dorsal stream functioning and other phenotypic traits that contrast with the autistic phenotype. Taken together these findings suggest that other mechanisms such as dorsal stream deficits (largest in WS) may underlie impaired central coherence.